Bacterial Behavior in Confined Spaces - Du, Hang; Xu, Weili; Zhang, Zhizhou; Han, Xiaojun (Frontiers in Cell and Developmental Biology, 2021)
In confined spaces, bacteria exhibit unexpected cellular behaviors, which are related to the biogeochemical cycle and human health. The types of confined spaces include lipid vesicles, polymer vesicles, emulsion droplets, microfluidic chips, and different lab-made chambers. In this mini-review, the behaviors of living bacteria in these confined spaces, including a) growth and proliferation, b) cell communication, and c) motion, are summarized. The future trends and challenges are also discussed in the paper.